Pengaruh Brand Image dan Country of Origin Terhadap Keputusan Pembelian Toyota - Hidayat, Ryan Jaya; Angelia, Wanda Dananina; Evelyn, Putri Angelica (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to find out whether brand image and country of origin influence the decision to purchase a Toyota brand car in the city of Palembang. This type of research is quantitative research. Research data was collected via Google Form. The sampling technique in this research is non- probability sampling with a purposive sampling method. The total sample collected in this study was 90 people. Data were analyzed using multiple linear regression statistical methods. The statistical application used is SPSS 23 software. The results of this research show that brand image (X1) influences purchasing decisions (Y), Country of origin (X2) influences purchasing decisions (Y) for Toyota brand cars.